Application of raw and differently dried Pineapple (Ananas comosus) pulp on Rasgulla (sweetened Casein Ball) to enhance its phenolic profile, shelf life, and in‐vitro digestibility characteristics. Issue 3 (2nd February 2021) - Sarkar, Tanmay; Salauddin, Molla; Pati, Siddhartha; Sheikh, Hassan I.; Chakraborty, Runu
Abstract: Pineapple is well known as a potential antioxidant‐rich fruit. The popular dairy product, rasgulla (sweetened casein ball) was fortified with raw pineapple pulp (PP), hot air‐ (PH), freeze‐ (PF), microwave‐ (PMW), and microwave‐convective (PMWC)‐dried pineapple pulp. The effect of fortifying rasgulla with pineapple on its nutritional quality, phytochemical profile, antioxidant activities, shelf life, in‐vitro digestibility, and mineral composition were studied. Phytochemical analysis showed the fortified samples were rich in alkaloids, flavonoids, polyphenols, sterols, tannins, and quinones. Fortification enhanced total polyphenol content (TPC), total flavonoid content (TFC), ferric reducing antioxidant activity (FRAP), 2, 2′‐Azinobis (3‐ethylbenzothiazoline‐6 sulfonic acid) radical scavenging property (ABTS), 2, 2‐diphenylpicrylhydrazyl (DPPH) radical‐scavenging capacity, hydrogen peroxide (H2 O2 ) radical scavenging activity, superoxide anion capture capacity (SO), and antioxidant capacity (AC). HPLC analysis showed that the fortification of rasgulla significantly increased the amount of seven polyphenols. Among all the rasgulla samples, PMWC showed the best results for most of the parameters. Novelty Impact Statement: This is the first approach to quantitate the phenolic profile of traditional Indian dairy product rasgulla (sweet syrupy cheese ball) and its pineapple fortified moiety. In this study, we opt to explore the nutritional profile of this novel dairy product very pertinent to the nutritional aspects of the dairy product and also the effect of antioxidant enrichment on the shelf life and in‐vitro digestibility is studied. Application of natural product to lower calorie intake during digestion may attract the end user more.